2017
DOI: 10.1111/1462-2920.13797
|View full text |Cite
|
Sign up to set email alerts
|

Following Rapoport's Rule: the geographic range and genome size of bacterial taxa decline at warmer latitudes

Abstract: We sought to test whether stream bacterial communities conform to Rapoport's Rule, a pattern commonly observed for plants and animals whereby taxa exhibit decreased latitudinal range sizes closer to the equator. Using a DNA sequencing approach, we explored the biogeography of biofilm bacterial communities in 204 streams across a ∼1000 km latitudinal gradient. The range sizes of bacterial taxa were strongly correlated with latitude, decreasing closer to the equator, which coincided with a greater than fivefold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
6
23
0
Order By: Relevance
“…Such investigations have revealed that, across spatial scales, bacterial communities typically show decreases in community similarity with increasing distance (Bissett et al ., ; Griffiths et al ., ). Bacterial communities have further been demonstrated to conform to macroecological patterns including the latitudinal diversity gradient (Lear et al ., ) and Rapoport's rule, where the geographic range sizes of organisms increase closer to the poles (Lear et al ., ). Soil bacterial communities are strongly influenced by pH, as well as other environmental variables such as plant diversity, C to N ratios or the moisture and clay content of soils (Lauber et al ., ; Griffiths et al ., ; Terrat et al ., ), whereas stream bacterial communities are strongly impacted by physicochemical parameters including sediment grain size and surface area (Mendoza‐Lera et al ., ), and seasonal temperature change (Hullar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Such investigations have revealed that, across spatial scales, bacterial communities typically show decreases in community similarity with increasing distance (Bissett et al ., ; Griffiths et al ., ). Bacterial communities have further been demonstrated to conform to macroecological patterns including the latitudinal diversity gradient (Lear et al ., ) and Rapoport's rule, where the geographic range sizes of organisms increase closer to the poles (Lear et al ., ). Soil bacterial communities are strongly influenced by pH, as well as other environmental variables such as plant diversity, C to N ratios or the moisture and clay content of soils (Lauber et al ., ; Griffiths et al ., ; Terrat et al ., ), whereas stream bacterial communities are strongly impacted by physicochemical parameters including sediment grain size and surface area (Mendoza‐Lera et al ., ), and seasonal temperature change (Hullar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Biogeography identifies patterns of diversity across defined spatial or temporal scales in an attempt to describe the factors which influence these distributions. Recent studies have shown that microbial community diversity is shaped across time and space 1 , 2 via a combination of environmental selection, stochastic drift, diversification, and dispersal limitation 3 , 4 . The relative impact of these ecological drivers on diversity is the subject of ongoing debate, with differential findings reported across terrestrial, marine, and human ecosystems 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have found that geographic ranges of environmental bacteria decrease towards the equator following Rapoport's Rule 4,5 . In addition, composition and diversity of environmental microbiomes vary with latitude [6][7][8][9][10] , and are known to be structured by abiotic factors, such as salinity, pH, temperature, oxygen and nutrients [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%